PENYULUHAN INFEKSI HEPATITIS B DAN PENCEGAHANNYA BAGI SISWA SISWI SEKOLAH MENENGAH KEJURUAN KESEHATAN DI DENPASAR - Kumbara, C.I.Y.K.; Wibawa, I.D.N.; Suryadarma, I.G.A.; Somayana, G. (Buletin Udayana Mengabdi; Vol 23 No 5 (2024): Buletin Udayana Mengabdi, 2023)
Hepatitis B infection still become a major health issue in Indonesia and in the World. The health care worker is the one of the populations that have a high risk of occupational exposure to blood borne diseases including Hepatitis B. Students of the Health Vocational High School also had a similar risk of exposure during their apprenticeship in hospital, but the information about risk of exposure and prevention of hepatitis B infection is very low. Therefore, we performed a health education about risk of exposure and prevention of Hepatitis B to the students as a form of community service activity. These activities were held in online setting on 6 July 2021. Among 74 participants there were 11,9% male, 88,1% female which are students and their teachers. The survey show, among participants 88% were never obtain the information about risk of Hepatitis B exposure related medical occupation, and 75% never had information about Hepatitis B vaccine. Based on evaluation of pre-test and post-test result, there is an increase in post-test score about 35% after the education were given. We expect this community health activity will increase the awareness of the Health Vocational High School students about the risk of Hepatitis B exposure and do the preventive measure such as get the Hepatitis B vaccination to prevent the Hepatitis B infection. Keywords: Prospective health workers, Hepatitis B, counseling, Vocational High School, vaccination